THE CAUSING FACTORS OF FISHERMEN POVERTY IN THE KEPENGHULUAN OF SINABOI SINABOI SUB DISTRICT ROKAN HILIR DISTRICT RIAU PROVINCE - Reza Kurnia Ndaru; Firman Nugroho; Zulkarnain Umar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research is about the causes of poverty fishermen communities in Kepenghuluan Sinaboi, Sinaboi Sub District, Rokan Hilir Regency, Riau Province, was held in April 2018. The research objectives were to (1) Determine the causes of fishermen's poverty in Kepenghuluan Sinaboi (2) Knowing the efforts of fishermen in facing poverty in Kepenghuluan Sinaboi (3) Knowing the government's efforts to solve the problem of poverty in Kepenghuluan Sinaboi. The research method used is a survey method with a qualitative approach. The sampling technique used was simple random sampling technique with a total of 30 respondents as fishermen. The results of this study indicate that the poverty of fishermen in Kepenghuluan Sinaboi is caused by 5 influential indicators: (1) The average income of fishermen households is IDR1.992.800,00 (2) Powerlessness of fishermen the ability to acces capital is very low (3) Vulnerability of fishermen in dealing with emergency situations due to lack of valuable assets if at any time they experience a disaster (4) Dependency, erratic fishing catches caused by the season (5) Alienation of fishermen, living places far from public facilities that are beneficial for fishermen. The efforts of fishermen to get out of poverty do not exist because of thoughts that only hope for government assistance. While the government's efforts to deal with the poverty of fishermen in Kepenghuluan Sinaboi are in the form of assistance but not yet fully felt by fishermen Keywords : Poverty, Fisherman, Goverment, The Kepenghuluan of Sinaboi.